Dead lions - Herron, Mick (Herron, Mick. Slough house, 2014)
London's Slough House is where washed-up M15 spies go to while away what's left of their failed careers. But now the 'slow horses' have a chance at redemption. An old Cold War-era spy is found dead on a bus outside Oxford, far from his usual haunts. As the agents dig into their fallen comrade's circumstances, they uncover a shadowy tangle of ancient secrets that seems to lead back to a man named Alexander Popov, and a decades-old conspiracy with a brand-new target: London's newest, tallest skyscraper ...